Pentraxin-3 modulates hepatocyte ferroptosis and the innate immune response in LPS-induced liver injury - Huitong Wang; Zhaojie Su; Yunyun Qian; Baojie Shi; Hao Li; Wenbin An; Yi Xiao; Cheng Qiu; Zhixiang Guo; Jianfa Zhong; Xia Wu; Jiajia Chen; et al. (Molecular Biomedicine)
Abstract The liver plays a crucial role in the immune response during endotoxemia and is one of the critical targets for sepsis-related injuries. As a secretory factor involved in inflammation, pentraxin-3 (PTX3) has been demonstrated to regulate hepatic homeostasis; however, the relationship between PTX3 and cell crosstalk between immune cells and hepatocytes in the liver remains incompletely understood. In this study, we revealed that, compared with WT mice, Ptx3 −/− mice with lipopolysaccharide (LPS)-induced endotoxemia exhibited alleviated liver damage, with reduced serum alanine transaminase and aspartate transaminase levels and an improved survival rate. Mechanistically, RNA-Seq and western blot results revealed that Ptx3 knockdown in hepatocytes increased the expression of Tfrc and Ccl20; consequently, Ptx3 deficiency regulated LPS-induced hepatocyte ferroptosis via increased mitochondrial reactive oxygen species and Fe2+ and recruited more macrophages by CCL20/CCR6 axis to be involved in inflammation and the clearance of harmful substances. Moreover, western blot and immunofluorescence staining confirmed that the NF-κB signaling pathway was upregulated upon LPS treatment in Ptx3-knockdown macrophages, promoting phagocytosis and polarization toward M1 macrophages. Collectively, our findings show that the absence of Ptx3 can ameliorate sepsis-induced liver injury by regulating hepatocyte ferroptosis and promote the recruitment and polarization of M1 macrophages. These findings offer a key basis for the development of effective treatments for acute infections.